RUMINAL CONDITION BETWEEN MADURA CATTLE AND ONGOLE CROSSBRED CATTLE RAISED UNDER INTENSIVE FEEDING - Umar, M.; Arifin, M.; Purnomoadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
Each four young bulls of Madura cattle and Ongole Crossbred (OC) cattle were used to study theefficiency of ruminal fermentation by comparing the proportion of Volatile Fatty Acid (VFA) of thesetwo breeds which were raised under intensive feeding. All the cattle were in about 1.5 years-old with anaverage body weight of 147.75 ± 14.57 kg and 167 ± 22.57 kg, for Madura and OC cattle, respectively.They were fed Napier grass (Pennisetum purpureum) hay, and concentrate feeding consists of pollard,soybean meal and rice bran for 10 weeks. Parameters measured were concentration of VFA at 0, 3 and 6h post-feeding and pH. The concentration of VFA in both Madura and OC cattle was peaked at 3 h postfeeding,being 136.1 mmol and 158.9 mmol, respectively, and then were decreased at 6 h post-feeding ata level of 58.1 and 98.2 mmol, respectively. The proportion of acetic acid in Madura and OC cattle were53.33% and 52.0% of total VFA, respectively, while the proportion of propionic acid and butyric acidwere 28.80% and 17.87% for Madura cattle, and 30.71% and 17.28% for OC cattle, respectively. Inaddition, the Acetic/Propionic ratios were 1.85 and 1.69 for Madura and OC cattle, respectively. RumenpH conditions of both cattle breeds tended to be basic, i.e. Madura cattle was ranged at 8.0-8.4, while thePO cattle was ranged at 7.6-8.4. In conclusion, both cattle breeds (Madura and OC cattle) have a similarefficiency to utilize the feeds in the rumen.